Doing Zimbabwean history with Terence Ranger: a personal note - Mazarire, Gerald C. (Taylor & Francis, 2016)
Terence Ranger had two physical moments in the academic history of Zimbabwe: the first, and most eventful, at the incipient stages of his illustrious career as a historian of Africa, and the second in the penultimate and twilight years of the same. Both were historiographically significant. I am associated with the second moment, to which I can give humble comment in the following lines, as it is also a moment that shaped my own career as a historian. It begins in 1998, when Terry arrived at the University of Zimbabwe (UZ) to teach the Master’s course in African History, which I took. This was a unique experience for the History department, which had experienced so much staff turnover since the 1970s guerrilla war, especially in the Master’s class. Never before had three of Zimbabwe’s celebrated historians been together under one roof and teaching the same class. Terry himself, Ngwabi Bhebe and David Beach took to this teaching assignment with as much energy as they devoted to research. Brian Raftopolous and ...